Translating innovative practices into organizational knowledge in the public sector: A case study. (24th May 2017) - Ferguson, Stuart; Blackman, Deborah
Abstract: Previous research suggests that innovation is heavily informed by strategic management theories and that there is little engagement with practice-based approaches. A case study of a public sector organization identified as doing something innovative is presented. Four main themes emerged. Two themes, the 'importance of a mandate' and the 'development of trust', had their foundations in traditional management practices. The others, 'capacity to challenge the norms' and 'boundary spanning', emerged from practice. It is suggested that a managerial approach that developed a supportive setting for innovation enabled the development of practices whereby innovation was effectively recognized, nurtured and sustained.